Russian Stock Market in Terms of Pierre Bourdieu's Theory of Social Space - Boris B. PODGORNY; Yuliya В. PODGORNAYA (Communications of International Proceedings, 2021)
We used the Bourdieu theory to study the Russian stock market as a new social field, where social forces are represented by agents, groups, organizations. Empirical base is the original sociological researches, conducted in Russia in 2006-2018.This article defines the stock market as a social field; shows its formation. This article defines the place of the stock market in the social sphere; shows its formation.
Keywords: Bourdieu's Theory; Stock market; social field; social forces.